Some contributions of human resources management to the development of the organization's and competitiveness of the organization - Loaiza Ospina, Diego Alberto; Loaiza Ospina, Diego Alberto; Loaiza Ospina, Diego Alberto (Corporación Universitaria Americana, 2011)
This article refers to the opportunity for any organization, whether micro, small, medium or large, public or privatesector, to recognize the incalculable value lies in its human capital as the main generator of value and differentiationin globalized world today. In the phenomena of globalization, Human Resource Management plays a strategic roleand leading role, it becomes the strategic partner that promotes change at all levels of the organization and allowsamong others, the transformation of organizational culture. Competitiveness is possible to achieve, but it needshuman management is aligned with the strategy and goals of the organization and an attitude of total commitmentand support from management.